2008
DOI: 10.1166/jnn.2008.18228
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions Alter Clay and Polymer Structure in Polymer Clay Nanocomposites

Abstract: In this work, using photoacoustic Fourier transform infrared spectroscopy (FTIR) we have studied the structural distortion of clay crystal structure in organically modified montmorillonite (OMMT) and polymer clay nanocomposites (PCN). To study the effect of organic modifiers on the distortion of crystal structure of clay, we have synthesized OMMTs and PCNs containing same polymer and clay but with three different organic modifiers (12-aminolauric acid, n-dodecylamine, and 1,12-diaminododecane), and conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Most importantly, the amount of clay in PCN influences the crystallinity of polymer and the mechanical properties [10]. Studies show that the properties of PCNs depend on individual phases and interaction between individual constituents [10][11][12]. Our previous work on PCNs has shown that the nonbonded interactions between different constituents alter the polymer phase [10][11][12] and thus significantly influence the mechanical properties of PCNs [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most importantly, the amount of clay in PCN influences the crystallinity of polymer and the mechanical properties [10]. Studies show that the properties of PCNs depend on individual phases and interaction between individual constituents [10][11][12]. Our previous work on PCNs has shown that the nonbonded interactions between different constituents alter the polymer phase [10][11][12] and thus significantly influence the mechanical properties of PCNs [1].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the properties of PCNs depend on individual phases and interaction between individual constituents [10][11][12]. Our previous work on PCNs has shown that the nonbonded interactions between different constituents alter the polymer phase [10][11][12] and thus significantly influence the mechanical properties of PCNs [1]. The organic modifier, which is used to modify the clay, has a significant influence on crystallinity of polymer and elastic modulus of PCNs [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Al-OH bending vibrations band at 916 cm−1 and Al-Fe-OH bending vibrations at 795 cm−1 were typical of bentonite clays. Consequently, the bentonite utilized in the present study was rich in aluminum and contained a portion of magnesium and iron too (Sikdar et al, 2008). The Si-O stretching band was seen at 1031.The broad peak at region 3426 cm −1 was recorded indicates the possible presence of alcohol -O-H, Phenol -OH group, or-NH groups in Bent.…”
Section: Characterizationmentioning
confidence: 84%
“…Our group has previously investigated nanoclays for preparation of bone tissue engineering scaffolds (Ambre, Katti, & Katti, ; Ambre et al, ; Katti, Katti, & Dash, ). These studies are based on a simulation‐based design methodology for design of polymer clay nanocomposites (Sikdar, Katti, & Katti, ; Sikdar et al, ; Sikdar, Katti, Katti, & Mohanty, ; Sikdar, Pradhan, Katti, Katti, & Mohanty, ).…”
Section: Introductionmentioning
confidence: 99%